Molecular dialogues between viruses and receptor‐like kinases in plants. (16th May 2019) - Macho, Alberto P.; Lozano‐Duran, Rosa
Summary: Receptor‐like kinases (RLKs) play a prominent role in the interaction between plants and extracellular pathogens. Intriguingly, in the past few years several studies have demonstrated that a number of RLKs influence plant susceptibility to viruses and, in some cases, interact with viral proteins. In this review, we will summarize and discuss recent advances suggesting a direct role for RLKs in plant–virus interactions.